One-step High Internal Phase Pickering Emulsions stabilized by uncracked micronized orange pomace. (July 2022) - Huc-Mathis, D.; Cafiero, M.; Hollestelle, C.; Michon, C.
Abstract: High Internal Phase Emulsions (HIPE) were formulated using 1% w /w orange pomace (i.e. uncracked micro-scaled byproduct powder) as sole stabilizer, from a quick and simple process, with 80% of sunflower oil and 20% of water in the liquid phase. Various indicators were monitored over a 2-month storage at Tamb, such as droplet size distribution, flow and viscoelastic properties, multi-scale microstructure (light and confocal microscopy). HIPPEs were stable towards coalescence and drainage, showing the complementarity between the anchoring insoluble fraction acting as Pickering particles at the oil-water interface and the viscosifying/film-forming soluble compounds. The oil droplet size distribution remained the same, and no significant change could be quantified regarding the elastic modulus, the yield stress or the viscosity of the emulsions in 60 days. However, changing the oil source from sunflower to another vegetal or synthetic oil could lead to unstable systems. Highlights: Proof of concept of clean-label High Internal Phase Pickering Emulsions is obtained. The only stabilizer is a small amount (1%) of micronized orange pomace powder. The emulsification is a cold, fast (2 min), simple (rotor-stator) and scalable process. This application can provide a high-value valorization of a vegetal by-product. The structuring mechanisms are hypothesized based on a multi-scale study.